Spacelord: Private and Secure Smart Space Sharing - Bae, Yechan; Banerjee, Sarbartha; Lee, Sangho; Peinado, Marcus (38th Annual Computer Security Applications Conference (ACSAC 2022), 2022)
Space sharing services like vacation rentals are being equipped with smart devices. However, sharing of such devices has privacy and security problems due to no or unclear control transfer between owners and users. In this paper, we propose Spacelord, a system to time-share smart devices contained in a shared space privately and securely while allowing users to configure them. When a user stays at a space, Spacelord ensures that the smart devices contained in it run code and configurations the user trusts while removing any pre-installed code and configurations. When the user leaves the space, Spacelord reverts any changes the user has introduced to the smart devices to delete any remaining private data and let the owner take back control over the devices. We evaluate Spacelord for two realistic space-sharing scenarios—smart home and coworking meeting room—and observe reasonable provisioning delay and runtime overhead.